Analysis of hemolysis activity of pathogenic bacteria on salted Lutjanus vivanus at Remu traditional market, Sorong city - Sukmawati Sukmawati; Cikita Putri Tania Tindoy; Sipriyadi Sipriyadi (Bioscience, 2022)
Fish is one of the fishery food ingredients needed by humans because fish meat has compounds that are needed by the body. These compounds consist of proteins, fats, carbohydrates, vitamins and mineral salts. Indonesia is an archipelagic country that has a lot of potential in agriculture and fisheries, and Sorong, West Papua, is no exception. The results of people's fisheries in Sorong, West Papua Province are quite high. Based on data from the Sorong City Fisheries Service, there are five types of fish that are exported abroad, such as China, Korea, and Japan. These types of fish include tuna, mackerel, bubarah fish, red snapper, and grouper or rock snapper. Stone snapper is not only consumed in the form of fresh fish, fish collectors also process it into dried salted fish. The purpose of this study was to analyze the hemolysis activity of pathogenic bacteria in salted snapper in the Remu market, Sorong city. This study is a descriptive study by providing a description of the object under study, namely the analysis of the hemolytic activity of pathogenic bacteria in salted rock snapper (Lutjanus vivanus) originating from the Remu traditional market in Sorong city. The conclusion of the research that has been carried out is that the hemolytic index of pathogenic bacteria for each sample shows the hemolytic index area from the highest to the lowest, sequentially from the untreated sample, namely the sample Do (110.0 mm), Ko (116.6 mm), To (453.3 mm), samples that were treated with frying before isolation were samples Dg (52.5 mm), Kg (3.5 mm), Tg (40.0 mm), while the smallest hemolytic index value was the sample that was boiled before The isolated samples were Dm (41.6 mm), Km (3.5 mm), and Tm samples (18.3 mm). Furthermore, all test samples showed β- hemolytic or total hemolytic.Ikan sangat dibutuhkan manusia sebab daging ikan memiliki senyawa-senyawa yang sangat dibutuhkan oleh tubuh. Senyawa-senyawa tersebut terdiri dari protein, lemak, karbohidrat, vitamin dan garam-garam mineral. Indonesia merupakan negara kepulauan yang memiliki banyak potensi dalam bidang pertanian maupun bidang perikanan, tidak terkecuali di Sorong Papua Barat. Hasil perikanan rakyat di Sorong Provinsi Papua Barat cukup tinggi. Berdasarkan data dari Dinas Perikanan Kota Sorong ada lima jenis ikan yang di ekspor keluar negeri seperti china, Korea, dan jepang. Jenis ikan tersebut diantaranya ialah ikan tuna, ikan tenggiri, ikan bubarah, ikan kakap merah, dan ikan kerapuh atau kakap batu. Ikan kakap batu selain dikonsumsi dalam bentuk ikan segar, para pengepul ikan juga mengolahnya ke dalam bentuk ikan asin kering. Adapun tujuan dari penelitian ini ialah untuk menganalisis aktivitas hemolysis bakteri pathogen pada ikan asin kakap batu di pasar Remu kota Sorong. Penelitian ini merupakan penelitian deskriptif dengan memberikan penggambaran tentang objek yang diteliti yaitu analisis aktivitas hemolisis bakteri patogen pada ikan asin kakap batu (Lutjanus vivanus) yang berasal dari pasar Remu kota Sorong. Adapun kesimpulan dari penelitian yang telah dilaksanakan ialah indeks hemolitik bakteri patogen untuk tiap sampel berturut-turut menunjukkan luas indeks hemolitik dari yang tertinggi hingga ke rendah, berturut-turut mulai dari sampel yang tidak diberikan perlakuan yakni sampel Do (110.0 mm), Ko (116.6 mm), To (453.3 mm), sampel yang diberi perlakuan penggorengan sebelum isolasi ialah sampel Dg (52.5 mm), Kg (3.5 mm), Tg (40.0 mm), sedangkan nilai indeks hemolitik yang paling kecil ialah sampel yang diberi perlakuan rebus sebelum diisolasi yaitu sampel Dm (41.6 mm), Km (3.5 mm), dan sampel Tm (18.3 mm). Selanjutnya seluruh sampel uji menunjukkan sifat β-hemolitik atau hemolitik total.